Utilizing Digital Technology in Church Youth Counseling: The "Teman Baomong" Platform Reaches the Unreached in the GMIT Classis in East Kupang City - Tiwuk Widiastuti; Adriana Fanggidae; Yuliyanto T. Polly; D.M Sihotang; N.D Rumlaklak; Marselino K.P. Abdi Keraf (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Adolescent mental health in East Nusa Tenggara Province has become an urgent concern due to increasing cases of emotional mental disorders and limited access to psychological services. To address this issue, the community service team partnered with the Klasis GMIT East Kupang City to develop the Teman Baomong Digital Platform as a web-based mental health consultation service for approximately 12,000 youth under the Klasis. This program aims to improve mental health literacy and access to psychological support that is safe, affordable, and stigma-free through online consultations with psychologists, religious leaders, and peer counselors, as well as the provision of educational content. The implementation methods included: (1) development of the Teman Baomong platform, (2) training of 35 peer counselors, (3) mental health education for 121 adolescents, and (4) provision of individual online consultation services. Evaluation was conducted through pre- and post-tests and a User Acceptance Test (UAT) to assess user acceptance of the platform. The results showed a significant increase in adolescent mental health literacy by 39.8% and enhanced involvement of peer counselors in community assistance. The UAT results from 50 respondents indicated an average score of 94%, demonstrating that the platform is perceived as highly effective and feasible for use. The highest-rated aspect was ease of use (98%), while the lowest was access speed (83.6%) due to internet network limitations in several congregation areas. In conclusion, the implementation of the Teman Baomong platform has effectively improved access to mental health services and literacy among adolescents, and it has strong potential for sustainable development within church and community support ecosystems in East Nusa Tenggara.